Factors associated with functional disability in patients with acute stroke excluded from alteplase administration due to minor non-disabling neurological deficits - Kim, Yong Jin; Choi, Seok Hong; Kim, Tae Young; Park, Hyeon-Mi; Shin, Dong Jin; Shin, Dong Hoon (Frontiers in Neurology, 2022)
Background: Although the PRISMS study did not demonstrate the benefit of intravenous alteplase administration in mild stroke patients within 3 hours, about 30% of patients presenting with mild symptom showed unfavorable functional outcomes. We investigated the factors predictive of functional disability at 90 days in patients who were excluded from alteplase administration due to National Institutes of Health Stroke Scale (NIHSS) scores of 0 to 5 and a score between 0 and 2 for each NIHSS score item. Methods: All patients were diagnosed with acute ischemic stroke or transient ischemic attack within 4.5 hours of admission to a tertiary hospital and did not receive alteplase due to minor stroke between January 2013 and December 2020. Radiological data and clinical information, including baseline and discharge NIHSS scores and modified Rankin Scale (mRS) scores at 90 days, were collected. Early neurological deterioration (END) was defined as an increase of two or more NIHSS scores. We defined moderate motor weakness as NIHSS limb motor score more than 3 and defined a favorable outcome as a mRS score at 90 days that was 0 or 1. Results: During the investigation period, 400 patients did not receive alteplase. END occurred significantly more frequently in patients with large artery disease (LAD) than in those with other TOAST classifications. In the multivariate regression analysis, NIHSS per 1-point increase, presenting as moderate motor weakness, and LAD were independent predictors of poor functional outcome (OR, 1.811 NIHSS per 1-point increase; 95% confidence interval [CI], 1.503-2.182; P<0.0001; OR, 2.173 moderate motor weakness; 95% CI, 1.028-4.595; P=0.042; OR, 2.033 LAD; 95% CI, 1.099-3.762; P=0.024, respectively). Conclusions: Moderate motor weakness presentation and LAD may be important factors associated with poor functional outcomes in acute stroke patients excluded from alteplase administration due to mild symptoms.